The response of climbing bean to fertilizer and organic manure in the northern province of Rwanda - Rurangwa, E.; Vanlauwe, Bernard; Giller, Kenneth E. (Cambridge University Press, 2020)
Climbing beans play a central role in food security of rural households in the densely populated highlands of East and Central Africa. Soil fertility degradation and the lack of nutrient inputs are major limitations to yield of beans and other crops. We conducted field trials in Northern Rwanda in Kinoni and Muko villages to evaluate the effect of mineral N, P, and K fertilizers (both alone and in combination) and farmyard manure on nitrogen fixation and grain yields of climbing bean in smallholder farmers’ fields. The trials were laid down in a randomized complete block design with seven replicate blocks in each village. Manure and fertilizer application led to greater yields in all fields, and the largest yields were achieved when manure was combined with NPK. Large variability in yield between fields was observed. Application of fertilizer together with manure increased the grain yield from 1.5 to 3.9 t ha−1 in Kinoni and from 2.6 to 5.4 t ha−1 in Muko. Fertilizer and/or manure increased stover yield from 0.8 to 2.3 t ha−1 in Kinoni and from 1.5 to 3.4 t ha−1 in Muko. Application of 30 kg P ha−1 and 5 t manure ha−1 led to increased N and P uptake (from 49 to 106 kg N ha−1 and from 6.1 to 12.4 kg P ha−1 in Kinoni and from 46 to 128 kg N ha−1 and from 5.3 to 17.9 kg P ha−1 in Muko). There was no clear relationship between soil fertility characteristics and the response of climbing bean to applied inputs at Muko site. However, at Kinoni site, limited response to manure and NPK application was observed in plots where soil available P and soil exchangeable K were relatively low. Our results show the benefits of using manure along with mineral fertilizers for increased climbing bean yields and nutrient uptake in smallholder farming systems.